The rapid shallow breathing index as a predictor of successful mechanical ventilation weaning: clinical utility when calculated from ventilator data - de Souza, Leonardo Cordeiro (J Bras Pneumol, 2015)
OBJECTIVE: The use of the rapid shallow breathing index (RSBI) is recommended in ICUs, where it is used as a predictor of mechanical ventilation (MV) weaning success. The aim of this study was to compare the performance of the RSBI calculated by the traditional method (described in 1991) with that of the RSBI calculated directly from MV parameters. METHODS: This was a prospective observational study involving patients who had been on MV for more than 24 h and were candidates for weaning. The RSBI was obtained by the same examiner using the two different methods (employing a spirometer and the parameters from the ventilator display) at random. In comparing the values obtained with the two methods, we used the Mann-Whitney test, Pearson's linear correlation test, and Bland-Altman plots. The performance of the methods was compared by evaluation of the areas under the ROC curves. RESULTS: Of the 109 selected patients (60 males; mean age, 62 ± 20 years), 65 were successfully weaned, and 36 died. There were statistically significant differences between the two methods for respiratory rate, tidal volume, and RSBI (p < 0.001 for all). However, when the two methods were compared, the concordance and the intra-observer variation coefficient were 0.94 (0.92-0.96) and 11.16%, respectively. The area under the ROC curve was similar for both methods (0.81 ± 0.04 vs. 0.82 ± 0.04; p = 0.935), which is relevant in the context of this study. CONCLUSIONS: The satisfactory performance of the RSBI as a predictor of weaning success, regardless of the method employed, demonstrates the utility of the method using the mechanical ventilator.